Dual-electrode pole piece of solid-state lithium metal battery and preparation method of dual-electrode pole piece

By adopting dual -electrode polar sheet structures in solid -lithium metal batteries, combining polymer substrate layers and collecting flow metal layers, the problem of lithium branches and metal lithium expansion has been solved, and more efficient battery preparation and better electricity have been achieved. Performance and security.

CN119381397APending Publication Date: 2025-01-28YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411585877.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Solid-state lithium metal batteries are prone to expansion of lithium dendrites and metal lithium during charging and discharging, resulting in diaphragm puncture, short circuits and deterioration of electrical properties, and are extremely challenging to production process control.

Method used

A dual -electrode pole sheet of a solid -state lithium metal battery, including polymer substrate layer, copper bearing layer, foam copper layer, aluminum layer, lithium metal layer, polymer solid electrolyte layer, and positive active material layer. The processing method is prepared to form a collection of flow metal layers to reduce lithium branches crystal production and expansion.

Benefits of technology

This dual -electrode chip isolates the positive and negative electrode through the polymer layer, reduces the production process of polar fragments and assembly sections, reduces the requirements for equipment accuracy, reduces the production and expansion of lithium branches, and improves the cycle performance and safety of the battery. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381397A_ABST
    Figure CN119381397A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode plates, and discloses a dual-electrode plate of a solid-state lithium metal battery and a preparation method of the dual-electrode plate. Comprising the following operation steps: depositing nano-copper on one side of a polymer base material layer to obtain a copper base layer; further depositing foamy copper on the surface of the copper base layer to obtain a foamy copper layer; a pole piece A is formed; depositing metal aluminum on the other side of the polymer base material layer in the pole piece A to obtain an aluminum layer; a pole piece B is formed; depositing metal lithium on the surface of the foamy copper layer in the pole piece B to obtain a metal lithium layer; further coating the surface of the lithium metal layer with an organic solution, and drying to obtain a polymer solid electrolyte layer; a pole piece C is formed; coating the surface of the aluminum layer in the pole piece C with positive active slurry, and drying to obtain a positive active material layer which is taken as a pole piece D; and rolling the pole piece D, respectively carrying out transfer welding on the aluminum layer on the positive electrode side and the copper layer on the negative electrode side, and leading out a metal foil tab to obtain the dual-electrode pole piece of the solid-state lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode plates, and in particular to a double-electrode plate of a solid-state lithium metal battery and a preparation method thereof. Background Art

[0002] The traditional lithium battery production method is to arrange the positive electrode, separator, and negative electrode alternately and combine them together by winding or stacking to form a roll core, which is then packaged, injected and sealed, and then undergoes formation testing to obtain a complete lithium battery. The electrode segment is divided into two units, the positive electrode and the negative electrode, which is also the most critical process for the electrochemical performance of the entire lithium battery, and requires very high process control and production precision; after the electrode is cut, the cut electrode is wound or stacked in the assembly process to form a roll core. In the assembly process, in order to increase the capacity of the battery cell and reduce safety risks, the alignment and coating margin of the electrode and separator become the difficulty of process control, which poses a great challenge to the production, equipment and process of each battery factory.

[0003] As the future development direction of lithium batteries, the biggest difficulty for solid-state lithium metal batteries is the generation of lithium dendrites and the expansion of metal lithium during charging and discharging. The generation of lithium dendrites will puncture the diaphragm and cause a short circuit. The high expansion of the lithium negative electrode will also cause the battery's electrical performance to deteriorate and the cycle rate to drop. In addition, lithium metal is extremely sensitive to moisture, which also poses a great challenge to the production process control. Once the process is out of control, it will not only affect the performance of the battery cell, but also may cause safety risks. Summary of the invention

[0004] The object of the present invention is to provide a double-electrode pole piece for a solid-state lithium metal battery and a preparation method thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A double-electrode pole piece of a solid-state lithium metal battery, comprising a polymer substrate layer, a copper base layer, a foam copper layer, an aluminum layer, a lithium metal layer, a polymer solid electrolyte layer, and a positive electrode active material layer.

[0006] A more optimized method for preparing a double-electrode pole piece of a solid-state lithium metal battery comprises the following steps: S1: using a polymer film as a polymer substrate layer, depositing nano copper on one side of the polymer substrate layer to obtain a copper base layer; S2: further depositing foam copper on the surface of the copper base layer to obtain a foam copper layer; this is the electrode A; S3: depositing metal aluminum on the other side of the polymer substrate layer in the pole piece A to obtain an aluminum layer; this is the pole piece B; S4: depositing metallic lithium on the surface of the foam copper layer in the electrode B to obtain a metallic lithium layer; S5: further coating an organic solution on the surface of the lithium metal layer and drying it to obtain a polymer solid electrolyte layer; this is the electrode C; S6: coating the positive electrode active slurry on the surface of the aluminum layer in the pole piece C, drying, and obtaining a positive electrode active material layer, which is the pole piece D; S7: The electrode piece D is rolled and transfer-welded on the aluminum layer on the positive electrode side and the copper layer on the negative electrode side, and the metal foil tabs are led out to obtain a double-electrode electrode piece of a solid-state lithium metal battery.

[0007] In the scheme, the dual-electrode pole piece includes a polymer film layer (polymer substrate layer), an aluminum layer on one side and a positive electrode active material layer outside the aluminum layer; a foam copper layer on the other side of the dual-electrode pole piece, a lithium metal layer outside the foam copper layer, and a solid electrolyte layer outside the lithium metal layer; the aluminum layer and the polymer film layer extend from one side to serve as the positive electrode ear, and the foam copper layer and the polymer film layer extend from the other side to serve as the negative electrode ear, and the positive electrode aluminum layer and the negative electrode copper layer are not connected to each other; the positive electrode ear and the negative electrode ear can be connected to the metal foil through transfer welding as the ear of the dual-electrode pole piece, which is convenient for subsequent welding and assembly processes.

[0008] More optimally, the thickness of the polymer substrate layer is 3μm~20μm; the thickness of the copper base layer is 5nm~100nm; the thickness of the foam copper layer is 1μm~5μm; the thickness of the aluminum layer is 0.5μm~2μm; the thickness of the lithium metal layer is 3μm~40μm; the thickness of the polymer solid electrolyte layer is 5μm~50μm; and the thickness of the metal foil tab is 4μm~10μm.

[0009] More optimally, the copper base layer is divided into an undeposited area and a deposited area in the width direction, the undeposited area is located on one side with a width of 5-20 mm, and the rest is a deposited area; The width of the copper foam is consistent with the size of the copper base layer; The aluminum layer is divided into an undeposited area and a deposited area in the width direction, the undeposited area is located on one side with a width of 5-20 mm, and the other is a deposited area; the undeposited area of ​​the aluminum layer and the undeposited area of ​​the foam copper layer are located in opposite directions; The width of the lithium metal layer is smaller than that of the copper foam layer, the lithium metal layer is located on the inner side of the copper foam layer in the width direction, and the width of the undeposited area reserved on the outer side of the copper foam layer is 5 mm to 20 mm; The polymer solid electrolyte layer completely covers the lithium metal layer; The positive electrode active material layer is located on the inner side of the aluminum layer in the width direction, and the width of the uncoated area reserved on the outer side of the aluminum layer is 5 mm to 20 mm.

[0010] More optimally, the positive electrode active slurry includes the following raw materials: 90%~98.5% of positive electrode active material, 0.5%~5% of binder, and 0.5%~5% of conductive agent, by mass fraction; the positive electrode active material includes one or more of nickel cobalt manganese, nickel cobalt aluminum, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, and lithium iron manganese phosphate.

[0011] More optimally, the density of the positive electrode active slurry is 100-300 g / ㎡.

[0012] More optimally, the aluminum layer on the positive electrode side uses one of aluminum, nickel and copper as the transfer welding electrode ear; the copper layer on the negative electrode side uses one of copper, nickel and aluminum as the transfer welding electrode ear.

[0013] Preferably, the polymer film includes at least one of polypropylene, polyethylene, polyethylene terephthalate, polyimide, polyphenylene sulfide, and polystyrene.

[0014] More optimally, the organic solution is a mixed solution of a polymer solid electrolyte and dimethylformamide or N-methylpyrrolidone; the polymer solid electrolyte includes one or more of polyvinylidene fluoride, polyethylene oxide, polypropylene oxide, polyvinylidene chloride, polyvinyl chloride, polyacrylonitrile, polymethyl methacrylate, polyacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethylethylene carbonate, and polyethyl cyanoacrylate.

[0015] More optimally, the copper base layer is deposited by physical deposition, including one of magnetron sputtering or evaporation; the foam copper layer is deposited by chemical reduction; and the aluminum layer and the metal lithium layer are deposited by vacuum evaporation.

[0016] In the lithium metal dual-electrode pole piece prepared by the above method, the middle polymer film layer plays the role of a diaphragm, which is equivalent to presenting the diaphragm, positive electrode, negative electrode, and solid electrolyte as a whole in the form of a dual-electrode pole piece. After the dual-electrode pole piece is prepared, only a single pole piece needs to be simply cut and wound (or cut and stacked) to form a core for subsequent welding and shelling processes. Compared with traditional battery cell preparation, there is no need to add additional diaphragms, and there is no need to worry about positive and negative electrode matching and alignment issues. This greatly simplifies the pole segment production process and reduces the control difficulty of the stacking or winding process. The equipment will be simpler and more efficient, and production efficiency will be greatly improved.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The two sides of the dual-electrode pole piece are the positive electrode and the negative electrode respectively, and the middle is separated by a polymer layer, which is equivalent to combining the positive and negative electrodes and the separator on the same pole piece, which can reduce the production process of the pole segment and the assembly segment.

[0018] (2) Single dual-electrode pole pieces are directly stacked / wound, which reduces the risk of scrap and short circuit safety caused by poor alignment during assembly and reduces the requirements for equipment accuracy.

[0019] (3) The negative electrode uses 3D copper as the current collector layer to reduce the formation of lithium dendrites and the expansion of the lithium negative electrode, reduce the stress in the electrode, and inhibit the expansion problem on the negative electrode side. During the charge and discharge process, the stress difference between the positive and negative sides is small, which can inhibit the curling of the electrode caused by unilateral expansion and improve the cycle.

[0020] (4) Solid electrolyte is directly coated on the surface of lithium metal to protect the lithium metal in the electrode segment, reduce the difficulty of process control, and reduce safety risks.

[0021] (5) The thickness of the current collector metal layer can be produced through processes such as composite and evaporation. The thickness is controllable, which can reduce the weight of the metal layer and increase the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the structure of the dual-electrode pole piece of the solid-state lithium metal battery of Example 2 of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0024] S1: Polyethylene terephthalate (PET, 100 mm in width, 1000 mm in length, 6 μm in thickness) was used as the polymer substrate layer. It was placed in a magnetron sputtering device with a pure copper target and evacuated to 1×10 -2 Pa, the sputtering power was adjusted to 1 kW, and a 30 nm thick nano-copper layer was deposited on one side of the polymer substrate layer to obtain a copper base layer; S2: A 2μm thick copper foam layer is further deposited on the surface of the copper base layer by chemical reduction to obtain a copper foam layer; this is used as the electrode A; the specific process method: the non-deposition area of ​​the PET film in S1 is protected with an acrylic plywood, and placed in a chemical plating solution containing copper ions, the plating temperature is 50°C, soaked for 2 minutes, then taken out for cleaning and drying. The main components of the chemical plating solution include 15g / L copper sulfate, 20g / L ethylenediaminetetraacetic acid, 9g / L sodium hydroxide, 4g / L formaldehyde, and 12g / L triethylamine.

[0025] The width of the copper foam is consistent with the size of the copper base layer; the copper foam layer does not cover the entire width of the polymer substrate layer, but reserves a 10mm blank area; S3: Place the electrode A into the vacuum aluminum evaporation equipment and adjust the vacuum degree to 1×10 -2 Below Pa, a layer of 1 μm thick aluminum is deposited on the non-copper side to obtain an aluminum layer; this is pole piece B; The aluminum layer does not cover the entire width of the polymer substrate layer, but reserves a 10 mm blank area, the position of which is opposite to the blank area of ​​the foam copper layer; S4: Under the dew point condition of -30℃, put the electrode B into the vacuum lithium evaporation equipment and adjust the vacuum degree to 1×10 -2 Below Pa, a layer of metallic lithium with a thickness of 8 μm is deposited on one side of the foam copper to obtain an aluminum layer metallic lithium layer; this is the electrode C; S5: coating the surface of the aluminum layer in the pole piece C with a lithium iron phosphate active slurry having a density of 180 g / ㎡, and drying it to obtain a positive electrode active material layer, which is the pole piece D; The positive electrode active material layer is located on the inner side of the aluminum layer in the width direction, and a 10 mm uncoated area is also reserved on the outer side of the aluminum layer as a reserved position for the tab; S6: rolling the electrode sheet D, respectively performing transfer welding on the aluminum layer on the positive electrode side and the copper layer on the negative electrode side, and leading out the metal foil tabs to obtain a double-electrode electrode sheet of a solid-state lithium metal battery; The double electrode sheets obtained in the above steps are cut into double electrode sheets with a width of 40 mm and a length of 100 mm along the width direction, with positive and negative pole ears on both sides of the length direction respectively; the double electrode sheets are alternately stacked with 10μm thick PP diaphragms (polypropylene diaphragms) to form a 5-layer stacked battery cell, and a small soft-pack battery is obtained through welding, packaging, baking, liquid injection and packaging processes.

[0026] Example 2 is based on Example 1: forming a 6 μm thick solid electrolyte coating layer outside the metal lithium layer; S1: Polyethylene terephthalate (PET, 100 mm in width, 1000 mm in length, 6 μm in thickness) was used as the polymer substrate layer. It was placed in a magnetron sputtering device with a pure copper target and evacuated to 1×10 -2 Pa, the sputtering power was adjusted to 1KW, and a 30nm thick nano copper layer was deposited on one side of the polymer substrate layer to obtain a copper base layer; S2: a 2 μm thick layer of foam copper is further deposited on the surface of the copper base layer by a chemical reduction method (same as in Example 1) to obtain a foam copper layer; this is used as the electrode A; The width of the copper foam is consistent with the size of the copper base layer; the copper foam layer does not cover the entire width of the polymer substrate layer, but reserves a 10mm blank area; S3: depositing a 1 μm thick layer of metal aluminum on the other side of the polymer substrate layer in the pole piece A by vacuum evaporation (same as in Example 1) to obtain an aluminum layer; this is the pole piece B; The aluminum layer does not cover the entire width of the polymer substrate layer, but reserves a 10 mm blank area, the position of which is opposite to the blank area of ​​the foam copper layer; S4: depositing a layer of metallic lithium with a thickness of 8 μm on the surface of the foam copper layer in the electrode B by vacuum evaporation (same as in Example 1) to obtain a metallic lithium layer; S5: further coating the surface of the lithium metal layer with a polyvinylidene chloride solution, drying it, and obtaining a 6 μm thick polymer solid electrolyte layer; this is electrode C; S6: coating the surface of the aluminum layer in the pole piece C with a lithium iron phosphate active slurry having a density of 180 g / ㎡, and drying it to obtain a positive electrode active material layer, which is the pole piece D; The positive electrode active material layer is located on the inner side of the aluminum layer in the width direction, and a 10 mm uncoated area is also reserved on the outer side of the aluminum layer as a reserved position for the tab; S7: The electrode sheet D is rolled and transfer-welded on the aluminum layer on the positive electrode side and the copper layer on the negative electrode side, and the metal foil tabs are led out to obtain a double-electrode electrode sheet of a solid-state lithium metal battery; the obtained double-electrode electrode sheets are then directly stacked to form a 5-layer stacked battery cell, which is then assembled into a small soft-pack battery.

[0027] Comparative Example 1 is based on Example 1: the copper base layer is thickened to 1 μm by water electroplating; S1: Using polyethylene terephthalate (PET, with a width of 100 mm, a length of 1000 mm, and a thickness of 6 μm) as a polymer substrate layer, a 30 nm thick nano-copper layer is deposited on one side of the polymer substrate layer by a physical deposition method (same as in Example 1) to obtain a copper base layer; S2: Place the primed polymer film into a copper electroplating tank, use pure copper as the anode, the polymer film as the cathode, and 200g / L copper sulfate solution as the electroplating solution. Set the current density to 3A / dm 2 , voltage 10V, temperature 50℃, thicken the copper base layer to 1μm thickness by water electroplating to obtain a copper layer; this is electrode A; The copper layer and the copper base layer have the same size; the copper base layer does not cover the entire width of the polymer substrate layer, but reserves a 10 mm blank area; S3: depositing a 1 μm thick layer of metal aluminum on the other side of the polymer substrate layer in the pole piece A by vacuum evaporation (same as in Example 1) to obtain an aluminum layer; this is the pole piece B; The aluminum layer does not cover the entire width of the PET base film, but reserves a 10mm blank area, the position of which is opposite to the blank area of ​​the copper base layer; S4: depositing a layer of metallic lithium with a thickness of 8 μm on the surface of the copper layer in the electrode B by vacuum evaporation (same as in Example 1) to obtain a metallic lithium layer; this is the electrode C; The metal lithium layer is located on the inner side of the copper layer in the width direction, and a 10 mm undeposited area is reserved on the outer side of the copper layer as a reserved position for the tab; S5: coating the surface of the aluminum layer in the pole piece C with a lithium iron phosphate active slurry having a density of 180 g / ㎡, and drying it to obtain a positive electrode active material layer, which is the pole piece D; The positive electrode active material layer is located on the inner side of the aluminum layer in the width direction, and a 10 mm uncoated area is also reserved on the outer side of the aluminum layer as a reserved position for the tab; S6: rolling the electrode sheet D, respectively performing transfer welding on the aluminum layer on the positive electrode side and the copper layer on the negative electrode side, and leading out the metal foil tabs to obtain a double-electrode electrode sheet of a solid-state lithium metal battery; The double electrode sheets of the solid-state lithium metal battery obtained in the above steps are cut into double electrode sheets with a width of 40 mm and a length of 100 mm along the width direction, with positive and negative ears on both sides of the length direction respectively; the double electrode sheets are alternately stacked with 10μm thick PP diaphragms (polypropylene diaphragms) to form a 5-layer stacked battery cell, and a small soft-pack battery is obtained through welding, packaging, baking, liquid injection, and packaging processes.

[0028] Performance Test: The batteries prepared in Comparative Example 1 and Examples 1-2 were tested for initial efficiency, rate, room temperature 1C cycle, DC impedance and other performances, and compared. The data are shown in Table 1: Table 1

[0029] Conclusion: Performance test results show that the first efficiency, rate, impedance, and cycle performance of the bipolar electrode using copper foam are better than those of the traditional copper foil bipolar electrode. When the polymer solid electrolyte replaces the diaphragm, the cycle and rate performance are further improved. This is because the copper foam promotes the transmission of electrons and hinders the formation of lithium metal side dendrites, improving the rate and cycle performance. The introduction of solid electrolyte shortens the distance between the positive and negative active materials, reduces the occurrence of side reactions at the positive and negative electrode interfaces, and thus improves the cycle performance.

[0030] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A double electrode plate for a solid-state lithium metal battery, characterized in that: The dual-electrode pole piece comprises a polymer substrate layer, a copper base layer, a foam copper layer, an aluminum layer, a lithium metal layer, a polymer solid electrolyte layer, and a positive electrode active material layer.

2. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 1, characterized in that: The steps include: S1: using a polymer film as a polymer substrate layer, depositing nano copper on one side of the polymer substrate layer to obtain a copper base layer; S2: further depositing foam copper on the surface of the copper base layer to obtain a foam copper layer; this is the electrode A; S3: depositing metal aluminum on the other side of the polymer substrate layer in the pole piece A to obtain an aluminum layer; this is the pole piece B; S4: depositing metallic lithium on the surface of the foam copper layer in the electrode B to obtain a metallic lithium layer; S5: further coating an organic solution on the surface of the lithium metal layer and drying it to obtain a polymer solid electrolyte layer; this is the electrode C; S6: coating the positive electrode active slurry on the surface of the aluminum layer in the pole piece C, drying, and obtaining a positive electrode active material layer, which is the pole piece D; S7: The electrode piece D is rolled and transfer-welded on the aluminum layer on the positive electrode side and the copper layer on the negative electrode side, and the metal foil tabs are led out to obtain a double-electrode electrode piece of a solid-state lithium metal battery.

3. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The thickness of the polymer substrate layer is 3μm~20μm; the thickness of the copper base layer is 5nm~100nm; the thickness of the foam copper layer is 1μm~5μm; the thickness of the aluminum layer is 0.5μm~2μm; the thickness of the lithium metal layer is 3μm~40μm; the thickness of the polymer solid electrolyte layer is 5μm~50μm; and the thickness of the metal foil tab is 4μm~10μm.

4. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The copper base layer is divided into an undeposited area and a deposited area in the width direction, the undeposited area is located on one side with a width of 5-20 mm, and the rest is a deposited area; The width of the copper foam is consistent with the size of the copper base layer; The aluminum layer is divided into an undeposited area and a deposited area in the width direction, the undeposited area is located on one side with a width of 5-20 mm, and the other is a deposited area; the undeposited area of ​​the aluminum layer and the undeposited area of ​​the foam copper layer are located in opposite directions; The width of the lithium metal layer is smaller than that of the copper foam layer, the lithium metal layer is located on the inner side of the copper foam layer in the width direction, and the width of the undeposited area reserved on the outer side of the copper foam layer is 5 mm to 20 mm; The polymer solid electrolyte layer completely covers the lithium metal layer; The positive electrode active material layer is located on the inner side of the aluminum layer in the width direction, and the width of the uncoated area reserved on the outer side of the aluminum layer is 5 mm to 20 mm.

5. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The positive electrode active slurry includes the following raw materials: by mass fraction, 90% to 98.5% of positive electrode active material, 0.5% to 5% of binder, and 0.5% to 5% of conductive agent; the positive electrode active material includes one or more of nickel cobalt manganese, nickel cobalt aluminum, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, and lithium iron manganese phosphate.

6. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The density of the positive electrode active slurry is 100-300 g / m 2 .

7. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The aluminum layer on the positive electrode side uses one of aluminum, nickel and copper as the transfer welding electrode lug; the copper layer on the negative electrode side uses one of copper, nickel and aluminum as the transfer welding electrode lug.

8. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The polymer film includes at least one of polypropylene, polyethylene, polyethylene terephthalate, polyimide, polyphenylene sulfide, and polystyrene.

9. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The organic solution is a mixed solution of a polymer solid electrolyte and dimethylformamide or N-methylpyrrolidone; the polymer solid electrolyte includes one or more of polyvinylidene fluoride, polyethylene oxide, polypropylene oxide, polyvinylidene chloride, polyvinyl chloride, polyacrylonitrile, polymethyl methacrylate, polyacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethylethylene carbonate, and polyethylcyanoacrylate.

10. The method for preparing a double electrode sheet of a solid-state lithium metal battery according to claim 2, characterized in that: The copper base layer is deposited by physical deposition, including magnetron sputtering or evaporation; the foam copper layer is deposited by chemical reduction; and the aluminum layer and the metal lithium layer are deposited by vacuum evaporation.

Citation Information

Cited By

  • Solid electrolyte membrane and preparation method thereof, secondary battery and electric equipment

    CN120149530A

  • Solid electrolyte membrane, method for manufacturing the same, secondary battery, and electric device

    CN120149530B